DIVERSITY AND ABUNDANCE OF INSECT AND SPIDER FAUNA IN SOLE AND SOYBEAN INTERCROPPED COTTON - C. SHANKER; BHARATI BHAT, K.R. MAHENDRA , G. ANITHA (The Journal of Research, PJTSAU, 2021)
Cotton, popularly known as the â€œwhite goldâ€Â in India is one of the important cash crops. India is theÂ second largest exporter of cotton in 2019 exporting 65Â lakh bales of 170 kgs and contributing 5% to agriculturalÂ GDP of our country and 11% to total export earnings.Â Insect pests constitute one of the major limiting factorsÂ in the production as the crop is vulnerable to attack by about 162 species of insects and mites (Sundarmurthy,Â 1985). In cotton, intercropping can provide resourcesÂ such as food and shelter and enhance the abundanceÂ and effectiveness of natural enemies (Mensah, 1999). Plant diversification increases the population of variousÂ natural enemies, which subsequently enhancesÂ natural pest control. For many species, natural enemiesÂ are the primary regulating force in the dynamics of their populations (Pedigo and Rice, 2009). Diversity of aÂ crop ecosystem can be increased by intercropping,Â trap cropping, presence of weeds or by crops grownÂ in the adjacent fields. When interplanted crops orÂ weeds in the crop are also suitable host plants for aÂ particular pest, they may reduce feeding damage toÂ the main crop by diverting the pest (Cromartrie Jr., 1993). The present study was taken up to quantify theÂ abundance and diversity of insect fauna in theÂ vegetative stage of cotton-soybean intercropped system and compare with the sole cropped systemÂ and to comprehend the impact of increased diversityÂ of natural enemies on pests in cotton.